Applications of Isotopes in Forensic Science - Filer, Crist N. (Journal of labelled compounds & radiopharmaceuticals, 2025)
ABSTRACT The existence of isotopes was proposed at the dawn of the 20th century based on compelling experimental evidence by many distinguished investigators. The subject of this review focuses on one specific application of isotopes in the evolving science of forensics. The topics covered include isotope ratio measurement and variation, forensic anthropology, wildlife trafficking, explosive investigation, illicit drugs, counterfeit medicines, food authentication, nuclear forensics and artificial intelligence (AI). Future directions and a conclusion for this important research topic are also included. This review describes the many applications of isotopes in forensic science.